PEMBELAJARAN MORAL DAN PEMAHAMAN NILAI (Pendekatan Developmental – Kognitif Terhadap Pendidikan Moral) - Susilawati, Samsul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
Lots of reasons that make education in moral and values is very important for children. One of them is because of the drugs abuse. Education in moral, teach about good and bad in behavior, actually in moral education there are two different side. They are physically and mentally. Values is about the truth and efficiency that hold people as a standart in behavior, the beauty of justice that should be done and kept. The conclusion of morality is the quality of what people do to show whether it is true or wrong, good or bad. Morality explains the meaning of good and bad in human behavior.Keyword: Moral, and Values